Effect of plant biomass, manure and inorganic fertilizer on maize yield in the central Highlands of Kenya - Mugwe, Jayne; Mugendi, Daniel N.; Kungu, James; Mucheru-Muna, Monicah (My University, 2007)
Soil fertility degradation remains the major biophysical cause of declining per capita crop production on smallholder farms in sub-Saharan Africa. Appropriate soil fertility regimes, are therefore, critical for improved crop productivity. This study investigated the feasibility of using sole organics or their combinations with inorganic fertilisers to improve maize (Zea mays) production in the highlands central Kenya. Sole application of Calliandra calotyrsus, Leucaena trichandra trichandra, Mucuna pruriens, Crotalaria ochroleuca, Tithonia diversifolia and cattle manure at 60 kg N ha-1 or combined application of the organic materials (30 kg N ha-1) plus inorganic fertiliser (30 kg N ha-1) gave significantly (P < 0.05) higher maize grain yields than the recommended rate of inorganic fertiliser (60 kg N ha-1). These treatments maintained maize yields at 4 to 6 t ha-1. Farmers had their own innovations where they combined organic resources and generally appreciable yields (3.0 to 5.6 t ha-1) were obtained from these innovations. However, there was a maize yield gap between on station and on farm trials with on station yields having on average 65% more yields than the on-farm yields. This was mainly attributed to differences in management practices arising from partial adoption of recommended rates. There is need therefore to develop and implement mechanisms tailored to ensure that farmers’ modications recommended soil amendment regimes and other agronomic practices are appropriate for enhanced crop productivity. Further studies are needed to establish the optimum mixture of different organic materials.
Keywords: Crop production; organic materials; soil fertility; Zea mays